Automated contouring, treatment planning, and quality assurance for total marrow lymphoid irradiation - Simiele, Eric; Hui, Caressa; Romero, Ignacio; Yang, Zi; Skinner, Lawrie; Xing, Lei; Ross, Jason B.; Hoppe, Richard T.; Binkley, Michael S.; Hiniker, Susan M.; Kovalchuk, Nataliya (Frontiers in Oncology, 2025)
PurposeTotal marrow and lymphoid irradiation (TMLI) enables dose escalation to targets while minimizing exposure to surrounding organs at risk (OARs), but its clinical implementation is complex. To simplify this process, contouring, treatment planning, and physics plan checks were automated, and the scripts were made publicly available.MethodsFifty patients (age, range 2-64 years) previously treated with volumetric modulated arc therapy total body irradiation (VMAT-TBI) were used for the development of an auto-contouring model to segment the relevant targets. Auto-contours were evaluated using the Dice Similarity Coefficient (DSC), 95% Hausdorff Distance (HD95), and qualitative ranking by four physicians. Automated planning script was created using the Varian Eclipse TPS API and was tested with ten patients: five plans using low-dose 2 Gy TMLI and five plans using high-dose 12 Gy TMLI. Dosimetric parameters, planning time, and blinded physician review were used to evaluate differences between auto and manual plans. Dosimetric differences between the VMAT-TMLI and analogous VMAT- TBI plans were also compared. Plan preparation for treatment and plan check processes were also automated to improve efficiency and to ensure safety and consistency.ResultsThe TMLI target auto-contours achieved an average DSC of 0.89 ± 0.03, HD95 of 3.38 ± 1.46, and a reviewers’ ranking of 1.12 ± 0.06, indicating close to “acceptable-as-is”. Compared to the manual VMAT-TMLI plans, the auto-plans demonstrated comparable dosimetric plan quality, with an average dose difference of –1.3% ± 5.9%. Five reviewers (four radiation oncologists and one medical physicist) selected the auto-plans as either equivalent or preferred 74% of the time. However, the required time for the auto-contouring and auto-planning was 4-5 hours compared to an estimated 2-3 days for manual contouring and planning. For both 2 Gy and 12 Gy prescriptions, the VMAT-TMLI plans achieved significantly greater OAR sparing compared to VMAT-TBI, with an average dose reduction of –34.1% ± 9.4%. Notably, the oral cavity, lenses, eyes, and salivary glands exhibited the most significant reductions, each exceeding 50% (all p ≤ 0.05).ConclusionsAn automated VMAT-TMLI planning process was developed, improving efficiency while maintaining clinical quality. The freely available scripts and documentation aim to standardize TMLI delivery and support multi-institutional trials.